Peran Fast Fashion, Brand Image, dan Social Influence terhadap Keputusan Pembelian This Is April Gorontalo - Siti Alfiah Manyoe; Melan Angriani Asnawi (Transbahasa, 2026)
This study aims to analyze the influence of fast fashion, brand image, and social influence on purchasing decisions for This Is April products at Citimall Gorontalo. This study employs a quantitative approach with a sample size of 97 respondents selected using probability sampling techniques. Data collection was conducted via an online questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that fast fashion and brand image have a positive and significant influence on purchasing decisions. Meanwhile, social influence does not have a significant partial effect. However, when considered simultaneously, all three variables have a significant influence on purchasing decisions. These findings suggest that trend alignment and positive brand perceptions are dominant factors. Additionally, the fashion industry adopting fast fashion trends appears to need to consider the quality of the products being sold, as this study found that sustainability indicators have a fairly strong influence on the consumer decision-making process.